2023
DOI: 10.1002/ijgo.14684
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality learning: A randomized controlled trial assessing medical student knowledge of fetal development

Abstract: Virtual reality (VR) is a technology that offers an immersive experience to promote discovery and exploration of personal knowledge and an opportunity to learn by doing, develop creativity, and increase understanding of less accessible concepts. 1 VR technologies can be characterized as a collection of hardware such as personal computers, head-mounted displays (HMDs), and tracking sensors,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A limitation of the current study is the small sample size, which may have led us to be under-powered to discover differences in knowledge acquisition. Additionally, as in previous studies ( 12 , 13 , 15 ), side-effects due to cybersickness are acknowledged as a limitation to the use of VR technology. However, with advancement of VR technology, and repeated exposure to the technology, side effects are expected to decrease ( 22 ).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…A limitation of the current study is the small sample size, which may have led us to be under-powered to discover differences in knowledge acquisition. Additionally, as in previous studies ( 12 , 13 , 15 ), side-effects due to cybersickness are acknowledged as a limitation to the use of VR technology. However, with advancement of VR technology, and repeated exposure to the technology, side effects are expected to decrease ( 22 ).…”
Section: Discussionmentioning
confidence: 80%
“…Medical students find immersive technology, such as VR, very enjoyable to use and adds to their overall learning experience ( 12 , 13 , 18 ). Previous research has demonstrated that students who are motivated and engaged by novel learning methods are more likely to retain knowledge, and may have improved learning outcomes ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immersive simulations reduced learning curves and offered safe alternatives to hazardous real-world practice. However, for some domains like acquiring textbook knowledge on fetal development, VR environments did not confer significant gains in test scores compared to traditional teaching methods, though they did improve student engagement and confidence(Ryan et al, 2023).…”
mentioning
confidence: 79%